Gnevyshev-Ohl rule for strong solar proton events - Ogurtsov, M.; Lindholm, M. (Elsevier Science Ltd, 2016)
Data on strong solar proton events, including: (a) instrumental record of ground level enhancements (1954-1996), (b) proxy record derived from nitrate series (1700-1944) and (c) proxy record derived from Be-10 series (1755-1927) were analyzed. It was shown that strong solar proton events are more frequent during even-numbered solar cycles than during odd-numbered ones with a probability of more than 0.93. The results provide new evidence for the fundamental character of the Gnevyshev-Ohl rule. Possible causes of the revealed even odd effect are discussed. (C) 2015 COSPAR.
Keywords: solar activity; solar proton events; Gnevyshev-Ohl rule; polar ice; nitrate; BE-10; cores; snow